Analisis Semiotika Barthes dalam Film Pirates of the Caribbean: Dead Men Tell No Tales terhadap Budaya Maritim Nusantara - Jesita Sani; Gheriya Ahmad (Besaung : Jurnal Seni Desain dan Budaya, 2026)
Semiotic and maritime mythological representations in the film Pirates of the Caribbean: Dead Men Tell No Tales using Roland Barthes semiotic approach. The research is conducted based on the assumption that film is not only an entertainment medium but also a cultural communication medium that produces signs, symbols, and myths through visual narratives. The purpose of this study is to analyze denotative, connotative, and mythological meanings in the film, identify narrative structures through Roland Barthes five narrative codes, and examine maritime cultural representations contextualized with Indonesian maritime culture. This research applies a descriptive qualitative method through observation, documentation, and visual analysis of scenes, dialogues, and symbols in the film. The findings reveal that the film constructs meaning through representations of sea curses, ghost ships, sea rulers, mysterious ocean territories, and sacred artifacts that shape modern maritime mythology. Barthes five narrative codes demonstrate that the film’s story structure is developed through mystery, conflict, visual symbolism, and cultural references that strengthen the fantasy adventure atmosphere. The study identifies symbolic correlations between the film’s mythology and Indonesian maritime culture, including the legends of SS Ourang Medan, the Masalembo Triangle, Nyi Roro Kidul, Keris Kyai Sengkelat, and the Larung Sesaji ritual practiced by Javanese coastal communities. This research shows that global popular films can be contextualized with local values through representations of maritime culture and mythology.